Discontinuation of carbamazepine due to concerns of long‐term consequences of enzyme induction. Issue 3 (8th June 2018) - Mäkinen, Jussi; Rainesalo, Sirpa; Raitanen, Jani; Saarinen, Jukka; Sandell, Satu; Peltola, Jukka
Summary: Objective: Treatment with carbamazepine (CBZ), a potent enzyme inducer, is known to affect the lipid profile, steroid, and vitamin D metabolism. Consequently, it has been postulated that patients on CBZ should be switched to noninducing antiepileptic drugs (AEDs). However, little is known about the seizure outcome following a CBZ switch in seizure‐free patients. We aimed to address this issue using a controlled observational study design. Methods: Fifty‐eight patients taking CBZ for focal epilepsy were assessed for discontinuing CBZ treatment due to concerns of long‐term adverse‐effects; 34 discontinued its therapy and 24 continued with CBZ. Six‐month seizure freedom was the primary end point. Furthermore, serum samples (total cholesterol (TC), low‐density lipoprotein (LDL), high‐density lipoprotein (HDL), triglycerides, sex hormone–binding globulin (SHBG), free testosterone, and 25‐hydroxyvitamin D levels from before and at least 3 months after discontinuation or continuation were obtained from all patients. Results: Seizure‐free patients had a 5‐fold elevated odds of seizure recurrence if CBZ was discontinued (95% confidence interval [CI 0.51–49.3; p = 0.17). A significant decrease in serum levels of TC, LDL, HDL, and SHBG as well as a significant increase in that of free testosterone were found in the discontinuation group compared with those who continued CBZ. Nonsignificant changes in triglycerides and vitamin D levels were detected. Significance: Discontinuation of CBZ in seizure‐free patients seems to carry a moderate, but legitimate, risk of relapse. Conversely, our results indicate that CBZ might have unfavorable effects on serum levels of TC, LDL, HDL, SHBG, and free testosterone.